DECISION SUPPORT SYSTEM FOR EMPLOYEE PERFORMANCE ASSESSMENT AT PERUM LPPNPI MEDAN BRANCH OFFICE USING THE METHOD AHP (ANALYTICAL HIERARCHY PROCESS) - Yudistira Aulia Masli; Arpan; Eko Haryanto (Sean Institute, 2022)
Employee performance appraisal is an important thing to do in order to improve employee competence so that a company can develop. Performance appraisals are also used for employees in promotions, positions, or company employees who are unable to comply with procedures. Perum LPPNPI is one of the offices that carries out employee performance appraisals. In conducting a performance assessment it is not appropriate because the system is still using a manual system. This problem causes performance appraisals to be a little difficult to determine the best employees based on established criteria. Decision support system is a suitable system for evaluating employee performance. The method used is the AHP (Analytical Hierarchy Process) method using the principle that the chosen alternative must have the closest distance from the positive ideal solution and the farthest from the negative ideal solution from a geometric point of view by using Euclidean distance to determine the closest distance from an alternative. to the optimal solution. By using a decision support system is expected to facilitate the company in assessing employee performance appropriately.